STUDI KEANEKARAGAMAN JENIS ANGGREK (Orchidaceae) BERDASARKAN KETINGGIAN TEMPAT DI BUKIT WANGKANG KABUPATEN KUBU RAYA - Damanik, Agus J; Kartikawati, S M; Prayogo, Hari (Universitas Tanjungpura, 2018)
Orchid is one of biological natural resources that need to be maintained its diversity, not only as a constituent of tropical forest ecosystem but it also have many benefits and potential to be managed. The purpose of this research was to study the diversity of species of natural orchids (Orchidaceae) at different altitudes located in Wangkang Hill within the Protection Forest Area of Bawang Mountain, Sei Ambawang Village. This research use multiple plot method with plot of field observation purposively. Total of observation plot is 16 plots and each plot measure 20 by 20 meters. So each plot has an area of 0.04 ha so that the total plot of the research is 0.64 ha. The results showed that in area of Wangkang Hill found as many as 16 species of natural orchids, with details of all types are epiphytic orchids. The number of individuals is 165 orchids. The index of species diversity (H') is more than one that is 1,103 and for each altitude ranges from 0.766 - 0.966, with the largest species diversity occurs at altitude of 300 - 345 m asl. This shows that at altitude of 300 - 345 m asl the grade of species diversity is high or the types that are found more than other altitudes.Keywords: Altitude, forest, orchid, species diversity.